BRIDGING THE GAP: STORE EXPERIENCE MEETS THE SUITABILITY OF VIRTUAL SHOPPING - Agarwal, Smriti; Shah, Vikita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The journey of virtual try-on technology traces back to the dawn of the Google age when e-commerce began reshaping our shopping habits. It arose as a solution to address the dilemmas posed by online shopping, where shoppers faced limitations in physically experiencing or testing products before committing to a purchase. [1.2]This gap between the physical in-store experience and the suitability of online shopping presented a prospect for innovation. As the technology evolved, so did its significance in the fashion industry. VTO emerged as the bridge between traditional in-store shopping and e-commerce, catering to the growing demand for a more engaging and immersive online shopping experience. It addressed the concerns of hesitant buyers, who were uncertain about how a garment would fit or how a shade of lipstick would look. [2,3,4]By providing a solution to these uncertainties, virtual try-on technology swiftly became an essential tool for fashion retailers, enhancing their customers’ shopping journeys.